Taxonomy of gelidiales in Malaysia based on molecular and morphological studies / Jelveh Sohrabipoor - Sohrabipoor, Jelveh (2013)
The Gelidiales is an important group of red algae that serves as a source of commercial agar and agarose. This order comprises three families and ten genera, of which Gelidium, Pterocladia, Pterocladiella and Gelidiella are the main sources of high quality agar and agarose. The Gelidiales is a very complicated order and the traditional classification of the order has been changed considerably based on modern molecular studies. Peninsular Malaysia and East Malaysia with extended coastlines in the Indo-Malayan ecozone have considerable potential of seaweed resources with 396 species reported in the latest checklist of the Malaysian seaweeds. Only eight species of Gelidiales have been reported for Malaysia. High morphological plasticity in the order Gelidiales attributed to the diverse ecological conditions, has resulted in many misidentifications using traditional taxonomy based on morphology. Molecular studies using modern tools have provided much basic molecular data to overcome the taxonomical complication of the order Gelidiales. In this study we hope to have a better understanding of the taxonomy of Malaysian Gelidiales. A combination of morphological study, as the traditional method, and molecular analyses as the modern method, was conducted to answer the question: Can the combination of molecular and morphological studies increase the number of Malaysian Gelidiales species or not?” Extensive collection of Gelidiales from the coastlines of Malaysia including Pulau Pinang, Pulau Langkawi, Pulau Pangkor, Pulau Besar, Port Dickson, Morib, Johor Baharu, Sabah and Sarawak has provided many specimens of Gelidiales for this study. In molecular studies after extraction of total genomic DNA of specimens collected in this study, partial sequences of three molecular markers including, rbcL, coxI and LSU were amplified and resulted in 98 sequences of these three genes. Phylogenetic analyses of the resulting sequences based on three methods, Maximum-likelihood, Maximum- parsimony and Bayesian inference, resulted in identification of thirteen morphospecies of Gelidiales from Malaysia. Four species were proposed as new species, including two new species in the genus Pterocladiella and two new species in the genus Gelidium. Two new records, Pterocladiella beachiae Freshwater, Pterocladiella bartlettii (W. R. Taylor) Santelices, one species of the genus Aphanta and three morphological forms of the genus Parviphycus, were the other new revelations of this study. Two previously reported species, Pterocladiella caerulescens (Kützing) Santelices & Hommersand and Gelidiella acerosa (Forsskål) Feldmann & G. Hamel were also verified based on both molecular and morphological studies. Two new records Pterocladiella bartlettii and Pterocladiella beachiae, which have already been reported from Caribbean Sea, southern and Central America, represent the first reports of these species from Southeast Asia and the Indo-Malayan ecozone. This study increased the number of Gelidiales in Malaysia from eight to 17 species and also provided detailed morphological data as well as molecular data on partial rbcL, coxI and LSU genes of the identified and studied species. These molecular markers can successfully differentiate the species of the Gelidiales at intraspecific, interspecific, intergeneric and family levels and additional studies based on these three markers may be able to resolve the problems of heterogenetic lineages such as Capreolia, Ptilophora and distant genera such as Pterocladia, Aphanta and Parviphycus.